Digital Transformation in Education: Emerging Trends and Best Practices Across Borders - Harris, Tamara B. (Jurnal Ar Ro'is Mandalika (Armada), 2022)
Digital transformation has become a prominent aspect of modern education, with emerging trends and best practices shaping educational landscapes across borders. This article explores the implications of digital transformation in education through a qualitative examination of literature and library research. By analyzing various studies and reports, this research aims to identify emerging trends and best practices in digital transformation across borders. The findings reveal several key themes, including the integration of digital technologies into teaching and learning, the use of data analytics for personalized learning experiences, the importance of digital literacy and skills development, the role of artificial intelligence and machine learning in education, and the impact of digital transformation on educational equity and access. Furthermore, this article discusses the challenges and opportunities associated with digital transformation in education, such as the digital divide, privacy concerns, and the need for professional development for educators. By synthesizing existing literature and research, this study provides insights into the current state of digital transformation in education and offers recommendations for policymakers, educators, and stakeholders to navigate and leverage the potential of digital technologies in shaping the future of education.